1996
DOI: 10.1038/nbt0896-975
|View full text |Cite
|
Sign up to set email alerts
|

Getting the glycosylation right: Implications for the biotechnology industry

Abstract: Glycosylation is the most extensive of all the posttranslational modifications, and has important functions in the secretion, antigenicity and clearance of glycoproteins. In recent years major advances have been made in the cloning of glycosyltransferase enzymes, in understanding the varied biological functions of carbohydrates, and in the accurate analysis of glycoprotein heterogeneity. In this review we discuss the impact of these advances on the choice of a recombinant host cell line, in optimizing cell cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
269
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(273 citation statements)
references
References 97 publications
1
269
1
2
Order By: Relevance
“…Host-cell type and culture conditions have been shown to be the most critical ones (Goto et al 1988;Goochee and Monica 1990;Jenkins et al 1996;Zhang et al 2002;Tomiya et al 2003;Yoon et al 2005). In particular, various elements of the extracellular environment, including the configuration of the production system (Watson et al 1994;Cabrera et al 2005;Lipscomb et al 2005;Spearman et al 2005) and the composition of the culture medium like ammonia concentration (Andersen and Goochee 1995;Borys et al 1994;Gawlitzek et al 1998;Jenkins and Curling 1994;Grammatikos et al 1998;Yang and Butler 2000a, b;Chen and Harcum 2005), glucosamine supplementation (Yang and Butler 2002), lipid availability , Na-butyrate addition (Lamotte et al 1999;Sung et al 2005) are able to affect protein glycosylation by potentially inducing changes in cell metabolism or favouring enzymatic product degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Host-cell type and culture conditions have been shown to be the most critical ones (Goto et al 1988;Goochee and Monica 1990;Jenkins et al 1996;Zhang et al 2002;Tomiya et al 2003;Yoon et al 2005). In particular, various elements of the extracellular environment, including the configuration of the production system (Watson et al 1994;Cabrera et al 2005;Lipscomb et al 2005;Spearman et al 2005) and the composition of the culture medium like ammonia concentration (Andersen and Goochee 1995;Borys et al 1994;Gawlitzek et al 1998;Jenkins and Curling 1994;Grammatikos et al 1998;Yang and Butler 2000a, b;Chen and Harcum 2005), glucosamine supplementation (Yang and Butler 2002), lipid availability , Na-butyrate addition (Lamotte et al 1999;Sung et al 2005) are able to affect protein glycosylation by potentially inducing changes in cell metabolism or favouring enzymatic product degradation.…”
Section: Introductionmentioning
confidence: 99%
“…It is now understood that murine cell lines, such as NS0 or SP2/0, contain the necessary biosynthetic machinery to produce proteins containing α-Gal epitopes [27][28][29] . However, it is generally accepted that CHO cells lack the biosynthetic machinery to synthesize glycoproteins with α-Gal antigens [30] . Some reports have revealed that CHO cells do not produce α-1,3-galactosyltransferase [31] and have a pattern of glycosylation that differs from that of the Erbitux host cell line Sp2/0.…”
Section: Wwwchinapharcom Yi Ch Et Almentioning
confidence: 99%
“…Unlike nucleic acids and proteins, oligosaccharides can be highly branched, and their biosynthesis proceeds in a non-template-directed fashion to produce complex mixtures of closely related structures that are difficult, if not impossible, to separate (2). Because subtle changes in the structures of these compounds can alter their properties dramatically (3), detailed studies of oligosaccharidemediated events require the use of homogeneous synthetic material (4). Oligosaccharide synthesis traditionally has been accomplished through the installation and removal of various orthogonally reactive protecting groups to differentiate each position of a monosaccharide substrate, and a similar procedure is used to synthesize glycosides and substituted monosaccharides in which 1 hydroxyl group is used as a handle for the introduction of small molecules or other functional groups (5).…”
mentioning
confidence: 99%